Preferences on advance care planning and end‐of‐life care in patients hospitalized for heart failure. (4th September 2021) - Kitakata, Hiroki; Kohno, Takashi; Kohsaka, Shun; Fujisawa, Daisuke; Nakano, Naomi; Shiraishi, Yasuyuki; Katsumata, Yoshinori; Nagatomo, Yuji; Yuasa, Shinsuke; Fukuda, Keiichi
Abstract: Aims: Early engagement in advance care planning (ACP) is recommended in heart failure (HF) management. We investigated the preferences of patients with HF regarding ACP and end‐of‐life (EOL) care, including their desired timing of ACP initiation. Methods and results: Data were collected using a 92‐item questionnaire survey, which was directly distributed to hospitalized patients by dedicated physicians and nurses in a university hospital setting. One‐hundred eighty‐seven patients agreed to participate (response rate: 92.6%), and 171 completed the survey [valid response rate: 84.7%; men: 67.3%; median age: 73.0 (63.0–81.0) years]. Logistic regression analyses were conducted to identify the predictors of positive attitudes towards ACP. Most recognized ACP as important for their care ( n  = 127, 74.3%), 48.1% stated that ACP should be initiated after repeated HF hospitalizations in the past year, and 29.0% preferred ACP to begin during the first or second HF hospitalization. Only 21.7% of patients had previously engaged in ACP conversations during HF management. Positive attitudes towards ACP were associated with lower depressive symptoms [two‐item Patient Health Questionnaire; odds ratio (OR): 0.75, 95% confidence interval (CI): 0.61–0.92, P ‐value: 0.006], marriage (OR: 2.53, 95% CI: 1.25–5.12, P ‐value: 0.010), and a high educational level (OR: 2.66, 95% CI: 1.28–5.56, P ‐value: 0.009), but not with severity of HF (represented by Seattle Heart Failure Model risk score). Regarding EOL care, while 'Saying what one wants to tell loved ones' (83.4%), 'Dying a natural death' (81.8%), and 'Being able to stay at one's favorite place' (75.6%) were the three most important factors for patients, preferences for 'Receiving sufficient treatment' (56.5%) and 'Knowing what to expect about future condition' (50.3%) were divergent. Conclusions: Despite patients' preferences for ACP conversations, there was a discrepancy between preference and engagement in ACP among patients hospitalized for HF. Patients' preferences regarding EOL care may differ; physicians need to consider the appropriate ACP approach to align with patients' care goals.